Edukasi Mitigasi Bencana Gempabumi dan Tsunami Bagi Siswa SMA Negeri 7 di Saparua, Maluku Tengah - Resti Limehuwey; Micky Kololu; Sitti Hafsa Kotarumalos; Robert Hutagalung; Philipus Josepus Patty (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
State Senior High School 7 Saparua in Central Maluku Regency is one of the schools located in an island region with potential vulnerability to earthquakes and tsunamis. This condition makes it important to develop students' knowledge and preparedness for disasters from an early age. This community service activity aims to provide education and understanding about earthquakes, tsunamis, and their mitigation to students. The method of implementation was carried out through material delivery, interactive discussions, and question and answer sessions related to earthquakes and tsunamis, as well as mitigation steps before, during, and after a disaster. The results of the activity showed that students showed high enthusiasm throughout the activity. This was evident in their active involvement in the discussion and various questions asked regarding the timing of mitigation implementation, appropriate mitigation strategies, and other factors that can trigger a tsunami. This activity provided students with an understanding of the importance of disaster preparedness. Through this activity, it is hoped that students of State Senior High School 7 Saparua will be able to increase awareness of disaster risks and disseminate this knowledge within the school and community.